(3CQHYhf MOjkKG aj LhGeY Gdcdes - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje eaJGM cd cJGH cQje hHYO agPg CQHYhf MOjKkG eHGfjgG jSjQI heYGfjgG cKjQI ef OQQ ZQQ SjO GdHTQ s
(3BNQgG (B:s
(3hgh MOjK MSf hESfGOg MSf QRbfG Gddg NdbkG MSfkG hQRbkG WjHkG hYdeG fGaYG hYedkG UGdMkG hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3jTJed Ydi ebOeI ai Yde GdcdGes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeLGejYs